Croton triqueter Lam.: efeito antitumoral e ativação da imunidade inata - SERRA, Izabel Cristina Portela Bogéa (2016)
The search for anticancer drugs has increased, with the aim of expanding the possibilities of treatments, to make them more effective and safe. In this work it was investigated the antitumor effect in vitro and in vivo of an ethanolic extract of Croton triqueter Lam. (EEJ) leaves, as well as possible mechanisms involved in this response. In addition, it assessed the effect of this extract on the immune system of healthy mice. For cytotoxicity evaluation was used the MTT assay, where the EEJ presented at all concentrations tested, cytotoxicity to Ehrlich carcinoma cells. On the other hand, only the highest concentration (500 µg/mL) reduced 20.4% the viability of RAW 264.7 macrophages. For evaluation of antitumor activity in vivo, Swiss mice, adult (± 60 days, 30 ± 5 g), male were inoculated intraperitoneally with the Ehrlich tumor cells (2x106 /animal) and treated on days 3, 5, 7, and 9 after tumor inoculation with EEJ at doses of 125, 250 and 500 mg/kg orally (po). The control group received phosphatebuffered saline (PBS), po. Furthermore, it was used a non-tumor bearing control group and treated with the same doses of EEJ and therapeutic regimen. Half of the animals were euthanized 10 days after tumor inoculation, the other half was kept alive for monitoring survival and calculation of life expectancy. The tumor development was evaluated by animal weight, waist circumference, ascites volume and total number of tumor cells. Whole blood was collected for determination of haematological parameters. Cytokines (IL-6, IL-10, TNF-α, IFN-, IL-12) and the chemokine MCP-1 present in the ascites and serum were measured by CBA technique. Spleen, bone marrow and mesenteric lymph nodes were obtained to perform the counting of lymphoid cells. After counting a portion of the spleen cell suspension was subjected to culture for assessment of NO production and another part was used to perform immunophenotyping by flow cytometry for T cells, NK, NKT cells and antigenpresenting cells. The results showed that the EEJ increased the lifespan of tumorbearing animals, and reduced the total number of tumor cells present in the peritoneal cavity. Besides, the EEJ in animals inoculated with tumor and the uninoculated not altered hematological parameters or the number of cells in the bone marrow and mesenteric lymph nodes. In the leukocyte differential count, EEJ was able to increase the number of lymphocytes and monocytes and reduce the number of polymorphonuclear leukocytes in mice inoculated with tumor and treated with EEJ. It was observed that in animals inoculated with or without Ehrlich tumor, EEJ at the dose of 500 mg/kg provided an increased number of spleen cells, and in animals inoculated with tumor there was an increase in the absolute frequency of CD4+ and CD8+ T cells, besides the increase of these populations expressing CD28+ marker, as well as increase of CD3-CD49b+NK1.1+ and IA-IE+Ly6C-Ly6G+CD86+ cells. The dose of 125 mg/kg increased the absolute frequency of CD4+ and CD8+ T cells activated, whereas the dose of 250 mg/kg only increased the population of CD8+ T cells activated. It was also found that the treatment with EEJ at three doses reduced the IL-6 concentration in the ascites dose-dependent manner, increased the IFN- concentration and only dose of 500 mg/kg reduced the TNF-α concentration. In serum, the dose of 125 mg/kg reduced the IL-6 concentration and increased IFN-. The analysis of EEJ on RAW 264.7 macrophages stimulated or not with LPS was possible to verify increased expression of CD14+ , IA-IE and CD86+ markers on macrophages with and without LPS, indicating that the EEJ has the ability to polarize macrophages to the profile M1. On macrophages polarization assay, EEJ was able to increase expression of IA-IE+ and CD86+ markers on previously polarized macrophages to the profiles M1 and M2. These results indicate that plant species Croton triqueter Lam. exhibits antitumor property, suggesting that, in addition to direct effects, immunological mechanisms were involved in this response.